(untitled) (The Macau Ricci Institute Journal, 2023)
When Pope Francis launched his message for the event “The Economy of Francesco” held online (November 19-21, 2020), he explicitly underlined the urgency “to enter into a covenant to change today’s economy and to give a soul to the economy of tomorrow” (Francis, May 1, 2019). For the last 15 months, more than 2000 young economists and entrepreneurs from 120 countries have been working, in a focused, organised way, to talk about the pillars of an economy based on the culture of care, true value creation and universal fraternity, moving beyond the still prevalent throwaway mentality and globalisation of indifference.